Self-service car washing machine and car washing system - MA CHENGLING; PANG HONG; QUAN JUNMIN (2018)
The invention provides a self-service car washing machine and a car washing system, and relates to the technical field of car washing. The self-service car washing machine comprises a central controller, a detecting unit and a steam unit; the detecting unit is used for detecting whether or not a current car is a reserved car and generating a control signal according to a detection result; the central controller is electrically connected with the detecting unit and the steam unit separately and used for obtaining the control signal and controlling the steam unit to be turned on or turned off according to the control signal. According to the technical scheme, the self-service car washing machine can achieve the reservation of automatic washing, after a car owner reserves car washing, the carowner can drive a car to the self-service car washing machine according to agreed time, after the car reaches a car washing area of the self-service car washing machine, the detecting unit can detectthe car which is currentl